Robert Merton and Contemporary Sociology - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 1997)
The purpose of the article is to introduce the reader with Robert Merton, whose text fragments are republished in this journal issue. Article discusses the significance of Robert Merton for the contemporary sociology. Aspects of historical development of sociological discipline are considered. The significance of Robert Merton’s and Talcott Parson’s works in defining sociology as a social science is emphasized. The article ends with an overview the biography of Robert Merton.